1987
DOI: 10.1159/000298798
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Blood Distribution of Zinc and Copper during Labor and after Delivery

Abstract: In 15 normal mothers the stress effects of labor on zinc and copper distributions in erythrocytes and plasma were investigated. Lower levels of total zinc and of zinc derived from both carbonic anhydrase isoenzymes (CA-I and CA-II), especially from CA-I, in erythrocytes were obtained immediately after delivery. On the other hand, there was a significant increase in total plasma zinc concentration only on admission to hospital in labor, although albumin-bound zinc concentration remained elevated throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…During pregnancy, Cu levels gradually rise from a prepregnancy level of about 120 mg/dL, in association with increased levels of circulatory estrogens and progesterone. In four separate studies, mean Cu levels at the end of the third trimester were reported in the range of 170-220 mg/dL [8][9][10][11]. Recently, Alebic-Juretic and Frkovic [12] reported that serum Cu levels in pathological pregnancies diagnosed during the first trimester were lower relative to those of normal pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, Cu levels gradually rise from a prepregnancy level of about 120 mg/dL, in association with increased levels of circulatory estrogens and progesterone. In four separate studies, mean Cu levels at the end of the third trimester were reported in the range of 170-220 mg/dL [8][9][10][11]. Recently, Alebic-Juretic and Frkovic [12] reported that serum Cu levels in pathological pregnancies diagnosed during the first trimester were lower relative to those of normal pregnancies.…”
Section: Introductionmentioning
confidence: 99%